Cemented Cruciate-Retaining Total Knee Arthroplasty in Osteoarthritis: A Comparison of Pegged and Stemmed Tibial Designs - Shah, Siddharth Mahesh; Dutton, Andrew Quoc; Liang, Shen; Ng, Geoffrey; Dasde, Shamal (The Journal of Knee Surgery, 2014)
We compared the clinical, functional, and radiographic outcomes between pegged (37 knees in 37 patients) and stemmed (33 knees in 31 patients) tibial designs in patients undergoing primary cemented total knee arthroplasty (TKA) for osteoarthritis (OA). Outcomes were evaluated using the knee society score (KSS-Clinical and Function scores) and knee injury and osteoarthritis outcome score (KOOS-pain, symptoms, stiffness, and function scores) at 6, 12, and 24 months postoperatively. Pre- and postoperative radiographs were evaluated for alignment and tibial coverage. All the outcome scores showed statistically significant improvement compared with the respective preoperative ones in both the groups at all points in time (p ≤ 0.039). None of the outcome scores were significantly different between the two groups at any point in time (p ≥ 0.06). Postoperative knee range of motion was also similar between the two groups at all points in time (p ≥ 0.641). Mean percentage tibial coverage was significantly greater in the pegged group as compared with the stemmed one (95.5% vs. 93.4%, p = 0.036). Incidence of complications (p = 0.617) and rates of revision (p = 1.000) were similar between the two groups. In conclusion, comparison of clinical and functional outcomes between the pegged and the stemmed tibial designs in TKA for primary OA did not reveal any significant difference at 2 years.
Keywords: osteoarthritis; total knee arthroplasty; tibial baseplate; pegged; stemmed